Bilateral bundle branch capture during deep septal myocardial and nonselective left bundle branch pacing preserves interventricular synchrony. (19th May 2022) - Curila, K; Jurak, P; Waldauf, P; Halamek, J; Stros, P; Smisek, R; Plesinger, F; Znojilova, L; Leinveber, P; Viscor, I; Herman, D; Osmancik, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health of the Czech Republic Background: Both left bundle branch pacing (LBBP) and deep septal myocardial pacing (LVSP) are less physiological than His bundle pacing. However, pacing both anode and cathode of the lead that is positioned in the interventricular septum may provide bilateral bundle branch capture, which may result in better interventricular synchrony. Objective: To use UHF-ECG to compare ventricular activation between HBp and bilateral bundle branch capture during left bundle branch (LBBPbi) and deep septal myocardial pacing (LVSPbi). Methods: Studies were performed in consecutive bradycardia patients. Bipolar pacing was performed with the lead in the LBBP (pseudo right bundle branch block morphology in V1 + proved LBB capture) and LVSP (pseudo right bundle branch block morphology in V1 without proved LBB capture) positions, with the pacing output leading to bilateral bundle branch capture. QRS duration was measured from the first to the last deflection of the QRS in any lead. UHF-ECG electrical dyssynchrony parameters – e-DYS (difference between the first and last ventricular activation) and local depolarization durations in precordial leads (V1-V8d) were calculated. Results: In 94 consecutive patients, measurements were performed during HBp (n = 75) and LVSPbi (n = 37) and LBBPbi (n = 64). The average pacing threshold leading to bilateral bundle branch capture was 2.6 V at 0.5 ms. nsHBp led to the shortest QRSd compared to sLBBPbi and LVSPbi (98 vs. 103 vs. 110 ms; p < 0.01). LVSPbi showed smallest e-DYS -2 ms vs. -8 ms during LBBPbi and 11 ms during nsHBp; p < 0.05, but V5-8d were during LVSPbi longer than during nsHBp and LBBPbi (absolute difference 4-9 ms); p < 0.05. No statistical difference in V5-V8d were observed between LBBPbi and nsHBp. Conclusion: Bilateral bundle branch capture during LVSP and nsLBBp preserves interventricular synchrony at the same level as HBp and thus leads to more physiological ventricular activation in patients with bradycardia.